2017
DOI: 10.1542/peds.2016-2215
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Conditions and Health Care Needs of Adolescents Born at 23 to 25 Weeks’ Gestation

Abstract: Adolescents born EPT have considerable long-term health and educational needs. Few had severe impairments that curtailed major activities of daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…An earlier study on this cohort showed that significantly more EPT children than term‐born controls had chronic conditions, including functional limitations (47% vs 6%), compensatory dependency needs (59% vs 27%) and services above those routinely required by children (64% vs 25%) . That study found that severe functional limitations affected just 7/132 (5%) EPT children with NSI at 10–15 years of age and these included being blind, difficulties with feeding, dressing and washing or being unable to walk . Table shows the consequences of chronic conditions identified in the three QUICCC domains in children with BPD, severe ROP and brain injuries, based on 132 of 134 (99%) survivors at 10–15 years as two declined to take part.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…An earlier study on this cohort showed that significantly more EPT children than term‐born controls had chronic conditions, including functional limitations (47% vs 6%), compensatory dependency needs (59% vs 27%) and services above those routinely required by children (64% vs 25%) . That study found that severe functional limitations affected just 7/132 (5%) EPT children with NSI at 10–15 years of age and these included being blind, difficulties with feeding, dressing and washing or being unable to walk . Table shows the consequences of chronic conditions identified in the three QUICCC domains in children with BPD, severe ROP and brain injuries, based on 132 of 134 (99%) survivors at 10–15 years as two declined to take part.…”
Section: Resultsmentioning
confidence: 96%
“…These included functional limitations, such as mental or emotional delays, the need for special services and spending reduced time and effort on activities, including being unable to play sports. It also included special arrangements in mainstream schools, full‐time separate classroom instructions, physical, occupational or other therapy and individual rehabilitation plans . In the multivariate models, the risk of having more than one consequence from chronic conditions in all three domains of the QUICCC was significantly higher among EPT children with BPD and brain injuries in the whole cohort and for BPD in the NSI‐free children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preterm birth can be regarded as a chronic health condition that has the potential to lead to functional limitations like intellectual disability, cerebral palsy, other motor problems and psychiatric conditions . Additionally, research has shown an increased risk of impaired lung function , reduced cardiorespiratory fitness and more cardio‐metabolic risk factors .…”
Section: Introductionmentioning
confidence: 99%